Urban Screen and Spatial Dimension - Litta Primasari; Basauli Umar Lubis (ITB Journal Publisher, LPPM ITB, 2013)
This paper is discussing about the urban screen phenomena and its influence to spatial dimension in urban space. The visual characteristics which are forming a spatial dimension will be an emphasis to be presented. Urban screen as a visual intervention has an impact to spatial configuration in urban space. The space dimension was not dominated with materiality limitation, but also images. We have to consider that people senses can measure a spatial dimension, knowing as a perception. That is a human visual and mind relation. The spatial dimension has no longer tangible boundary, but also has intangible ones. Spatial dimension in urban screens phenomena is not merely mathematics, nor spatial dimension in physics which are based on a three-dimensional Cartesian coordinate system. Movement can be expressed in other terms, by how far we can move depends on our eyes to catch that space limitation, and how fast we can move is depends on our mind to perceive some visual phenomenon, that is a spatial dimension. So, the dimension will depend on a visual quality that we perceived. The movement of the body and people's thought will be an important term to generate the space dimension in urban screen phenomenon. The activity of body's movement and thought will influence the depth of space dimension.